2021
DOI: 10.1177/1747493021991969
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis in stroke with admission NIHSS score 0 or 1

Abstract: Background Up to 30% of stroke patients initially presenting with non-disabling or mild deficits may experience poor functional outcome. Despite, intravenous thrombolysis remains controversial in this subgroup of stroke patients due to its uncertain risk benefit ratio. Aim We aimed to analyze the real-world experience with intravenous thrombolysis in stroke patients presenting with very low NIHSS. Methods Data of stroke patients presenting with mild initial stroke severity (NIHSS 0–5) including vascular risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 27 publications
4
22
1
1
Order By: Relevance
“…In our minor stroke cohort, intravenous thrombolysis was not associated with outcome. Although we did not assess this association further, existing results have shown that thrombolysis may be associated with potential harm in patients presenting with an NIHSS score of 0-1 compared to patients with a score of 2-5 (21). Other results suggested that intravenous thrombolysis might also be associated with deterioration due to thrombus fragmentation in some patients with ICA occlusion (22).…”
Section: Discussionmentioning
confidence: 86%
“…In our minor stroke cohort, intravenous thrombolysis was not associated with outcome. Although we did not assess this association further, existing results have shown that thrombolysis may be associated with potential harm in patients presenting with an NIHSS score of 0-1 compared to patients with a score of 2-5 (21). Other results suggested that intravenous thrombolysis might also be associated with deterioration due to thrombus fragmentation in some patients with ICA occlusion (22).…”
Section: Discussionmentioning
confidence: 86%
“…Inclusion criteria: treatment-naive patients with confirmed diagnosis of CI; the National Institutes of Health Stroke Scale (NIHSS) score ≥ 1 point [ 15 ]; no previous history of craniocerebral trauma, cerebrovascular events, or encephalitis.…”
Section: Methodsmentioning
confidence: 99%
“…ey extracted and analyzed from a large national stroke registry [3]. Zhang et al have studied the incidence, composition, and outcomes of END after acute ischemic stroke by IVrt-PA and EVT and identified risk factors for END [4].…”
Section: Related Workmentioning
confidence: 99%